PERSEPSI WISATAWAN GEN Z DAN MILLENIAL TERHADAP PENANGANAN KELUHAN DIGITAL DAN DAMPAKNYA PADA CITRA DESTINASI WISATA HUTABALIAN - Handayani Silalahi, Riana (Penerbit Lafadz Jaya, 2025)
Hutabalian Tourism Village in Sianjur Mula-Mula District, Samosir Regency, North Sumatra, is a cultural tourism destination rich in the history and spirituality of the Toba Batak people. With its stunning natural landscape and strong traditional preservation, the village attracts both local and international tourists, especially those from Generation Z and Millennials who are familiar with digital technology. However, the increase in visits from these digital-native tourists brings new challenges, particularly in terms of complaint management and digital interactions. This study aims to analyze the perceptions of Gen Z and Millennial tourists towards the digital complaint handling system implemented in Hutabalian Tourism Village, identify the challenges faced by village management, and evaluate its impact on the destination's image. The study used a qualitative phenomenological approach with data collection techniques through in-depth interviews, observation, and digital documentation. Informants consisted of Pokdarwis (tourism group), homestay and MSME operators, as well as Gen Z and Millennial tourists who had visited and submitted complaints digitally. The analysis was conducted using the Colaizzi model with SWOT reflection as a strategic interpretation. The study results show that tourists have a high appreciation for the cultural richness and authenticity of Hutabalian Tourism Village, but regret the suboptimal response to digital complaints. Complaints related to facilities, road access, and limited digital information are primary concerns. Meanwhile, the Tourism Awareness Group (Pokdarwis) stated that limited human resources and digital infrastructure are the main obstacles to providing adequate digital services. The absence of a dedicated social media administrator and the limited involvement of the younger generation in digital management exacerbate this situation. Despite this, Hutabalian Village maintains a positive image thanks to its strong cultural appeal and spiritual experiences. The study concludes that the quality of digital complaint handling directly impacts the perception and image of the destination in the eyes of digital tourists. This study recommends strengthening the capacity of local digital human resources, establishing a social media management team, and cross-sector collaboration to achieve tourism destination management that is adaptive to changes in digital tourist behavior.